International students motivations for studying in UK Higher Education: Understanding choice and decision making process of Indian students. - Arora, Vikas (2007)
Globalisation and internationalization of economies has led to the commercialisation of higher education. The education sector has become an increasing important sector and the developing countries have become lucrative markets for the same. Various countries like the UK have recognized this need and have responded with renewed marketing campaigns. Various activities, shows on television sponsored by universities, opening up of university campuses in South East Asia (University of Nottingham, China Campus) are a few examples. In recent years India has achieved a fascinating economic growth rate. The coming in of multi national companies has created new jobs and the demand of educated employees has grown tremendously. Due to this there has been a massive increase in the consumption of education both in the country and abroad. The Indian market has thus become extremely important. The UK Higher education system has always been considered to be one of the best, only second to the US. Due to recent entry of Australia and other countries like New Zealand in the higher education sector, the competition to recruit international students has become extremely intense. Even though the number of Indian students coming to the UK to pursue their higher education has constantly been increasing, the actual growth rate is decreasing every year. The universities need to understand the importance of the Indian market and have to take steps to ensure that more and more Indian students come to the UK for their higher education. The research carried out tries to understand the decision making process of Indian students which will help the universities not only understand the Indian student better but give them an opportunity to tailor their marketing efforts in a way to attract and recruit more Indians and to target appropriate segments. The role and importance of the agents is also discussed and recommendations given to improve the network of agents in the country. The importance of alumni and word-of-mouth referrals is also highlighted with the help of the research.